Relative influence of noncovalent interactions on the melting points of a homologous series of 1,2-dibromo- 4,5-dialkoxybenzenes - Fonrouge, A. (2013)
Crystal structures are presented for two members of the homologous series of 1,2-dibromo-4,5-dialkoxybenzenes, viz. those with decyloxy and hexadecyloxy substituents, namely 1,2-dibromo-4,5-bis(decyloxy)benzene, C26H44Br2O2, (II), and 1,2-dibromo-4,5-bis(hexadecyloxy)benzene, C38H68Br2O2, (III). The relative influences which halogen bonding, π- π stacking and van der Waals interactions have on these structures are analysed and the results compared with those already found for the lightest homologue, 1,2-dibromo-4,5- dimethoxybenzene, (I) [Cukiernik, Zelcer, Garland & Baggio (2008). Acta Cryst. C64, o604-o608]. The results confirm that the prevalent interactions stabilizing the structures of (II) and (III) are van der Waals contacts between the aliphatic chains. In the case of (II), weak halogen C - Br ⋯(Br - C) ′ interactions are also present and contribute to the stability of the structure. In the case of (III), van der Waals interactions between the aliphatic chains are almost exclusive, weaker C - Br ⋯ π interactions being the only additional interactions detected. The results are in line with commonly accepted models concerning trends in crystal stability along a homologous series (as measured by their melting points), but the earlier report for n = 1, and the present report for n = 10 and 16, are among the few providing single-crystal information validating the hypothesis.